2012
DOI: 10.4097/kjae.2012.63.2.149
|View full text |Cite
|
Sign up to set email alerts
|

Effect of superoxide on the development and maintenance of mechanical allodynia in a rat model of chronic post-ischemia pain

Abstract: BackgroundReactive oxygen species and inflammatory responses contribute to the development of neuropathic pain. Superoxide serves to mediate cell signaling processes and tissue injury during inflammation. We examined the effects of superoxide on the development and maintenance of mechanical allodynia, as well as its contribution to central sensitization in a superoxide-rich animal model of neuropathic pain.MethodsChronic post-ischemia pain (CPIP) was induced via the left hindpaw ischemia for 3 h, followed by r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…There is accumulating evidence that the interaction between MAPK activation and ROS is linked to diverse pathologic conditions including IR injury, neuropathic pain [28], and inflammatory disease [29]. In a previous study, we found that ROS led to mechanical allodynia through central sensitization by N-methyl-D-aspartate (NMDA) receptor activation in the spinal cord [30]. This prompted us to hypothesize that ROS may activate intracellular signaling pathways in the spinal cord.…”
Section: Discussionmentioning
confidence: 97%
“…There is accumulating evidence that the interaction between MAPK activation and ROS is linked to diverse pathologic conditions including IR injury, neuropathic pain [28], and inflammatory disease [29]. In a previous study, we found that ROS led to mechanical allodynia through central sensitization by N-methyl-D-aspartate (NMDA) receptor activation in the spinal cord [30]. This prompted us to hypothesize that ROS may activate intracellular signaling pathways in the spinal cord.…”
Section: Discussionmentioning
confidence: 97%
“…The mechanical allodynia of CPIP rat B A L1 1 1 1 1 1 1 1 1 1 1 1 1 1 1 1 1 1 1 1 1 1 1 1 1 1 1 1 1 1 1 1 1 1 1 1 model can fully develop within 3 days and maintain thereafter. 8,14 Thus we waited 4 days after the model establishment and applied 2/100 Hz EA to rats on day 4. We found that EA can still produce robust antiallodynic effect on both ipsilateral and contralateral hind paw of CPIP model rats (Supplement Fig 1).…”
Section: Ea Significantly Attenuates the Mechanical Allodynia In Cpipmentioning
confidence: 99%
“…Future research should examine prolonged hind limb ischemia-reperfusion, which is known to induce inflammatory cascades and contribute to the formation of reactive oxygen species (1,7,(40)(41)(42)(43).…”
Section: Wwwpainphysicianjournalcommentioning
confidence: 99%